Cover Image, Volume 60, Issue 1. Issue 1 (9th March 2020) - Unknown
Abstract: On the cover : Genetic diversity is the key to sustaining sunflower as viable global crop. Phenotypic and genotypic data is the key to efficiently utilize this diversity. See Terzić et al. Photo credit: Sreten Terzić.